Offenheit als ethisches Problem : informationsethische Grundpfeiler und Open Access-Repositorien: eine Analyse auf Grundlage von Fachliteratur und Expertenbefragung - Wolf Thomas Trüter (2021)
Information ethics are part of applied ethics and are concerned with themes like data protection, informational autonomy, the right of free access to knowledge and information as well as information justice. Open Access-repositories are a type of digital archives, containing freely accessible scientific publications. There are a number of quality criteria which apply to such repositories and which are also part of a concept of long term archiving and supporting scientists, who want to publish in a freely accessible way. This thesis tries to demonstrate that infor-mation ethical core issues such as the right to informational autonomy, informa-tional justice and the right of free access to scientific publications can also be ap-plied to Open Access-repositories.
Keywords: Informationsethik; Open Access; Repositorien; Informationsgerechtigkeit; Informationstechnologie; Kommunikationstechnolgie